Culinary Product Quality on Purchasing Decisions and Consumer Satisfaction as Interverning Variables: The case of Gabus Pucung as a Halal culinary icon for the Betawi Ora community in Bekasi, Indonesia - Untari, Dhian Tyas (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
Bekasi is one of Jakarta's buffer zones where strong socio-cultural interactions occur. Culinary in a society is a reflection of the relationship between humans and humans individually, humans and society communally and human relations with their environment. One of the culinary delights that is very famous and in high demand is Gabus Pucung. With the high competition and business challenges of the Gabus Pucung culinary provider, this study aims to: 1) analyze whether there is an effect of product quality on consumer satisfaction, 2) whether there is an effect of consumer satisfaction on purchasing decisions and 3) whether there is an indirect effect of product quality through consumer satisfaction on purchasing decisions. Sampling uses a systematic sampling technique which is included in the category of non-probability sampling. Samples were taken of ± 30 people per district (12 districts), so that a total sample of 360 people was obtained as respondents in this study. The results of the study stated that the relatively high demand for Gabus Pucung culinary demanded marketers and culinary providers of Gabus Pucung to be able to continue to maintain product quality to increase consumer satisfaction, where this satisfaction has implications for returning decisions.